The Guatemalan Mayan- Achi’ religiosity as the foundation of their cultural identity - Caballero Mariscal, David (Revista Cultura y Religión, 2017)
In the general context of Guatemala, characterized by its ethnic and cultural diversity, and predominantly indigenous, the achi’ people constitute less than one per cent of the total population. Nevertheless, and despite they have suffered from the imposition of diverse cultural groups, and a cruel genocide as well, they still preserve a significant part of their cultural heritage, including the language, traditional dances, the Rabinal achi’ and diverse religious expressions, guarantor of their cultural identity. This research attempts to fill the gap on this ethnical group, due to owing to the current absence of studies about the Ach´ies. Likewise, it tries to delve into the adaptation and syncretism mechanisms this collective has develop, culturally and religiously, as a means of survival through new ways of transculturation. These guarantee the continuity of the Mayan traditional culture and religiosity, in the context of the current catholic faith, predominant among the members of this Mayan people.